Redução de proteína bruta em rações para suínos machos castrados na fase inicial, submetidos a diferentes condições térmicas - Freitag, Debora Cristiane (2012)
This study aimed to evaluate the reduction of crude protein ration on nitrogen balance, blood parameters, and physiological urinary pH of barrows in the initial phase in stress condition (28,77 ˚C) and thermal comfort (18,13 ˚C). For the experiment we used 32 barrows in the initial phase, with initial mean body mass of 18,5 ± 0,73 kg. The animals were divided into two experiments in two environmental conditions (stress and thermal comfort) in a randomized complete block with four decreasing levels of crude protein (20,5; 19,4; 18,3 and 17,2%) with four replications, totaling 16 plots in each experiment. Each plot consisted of an animal, totaling 32 animals. The parameters analyzed were ingested nitrogen, excreted in feces and urine, absorbed, retained, retained/absorbed, total excretion, net protein utilization (ULP), cholesterol, triglycerides, glucose, urea, creatinine in blood plasma, urine pH, respiratory rate, rectal temperature and body. In heat stress condition, reducing the crude protein content of the diet decreased the nitrogen excreted in the urine, the total excretion and plasma triglyceride in growing pigs. For thermal comfort condition in growing pigs had higher nitrogen ingested, absorbed, retained and, of plasma urea. The response surface for rectal temperature, body temperature and respiratory rate increased, in function to ITGU and different times of observation, being more evident in thermal comfort condition